Assessment of the impact of HIV infection on the hypothalamic-pituitary-ovarian axis and pubertal development among adolescent girls at a tertiary centre in Zimbabwe: a cross-sectional study - Bothwell Takaingofa Guzha; Bismark Mateveke; Hamish Mubata; Tapiwa Chapupu; Vongai Dondo; Maxwell Chirehwa; Rendani Tshikosi; Tsungai Chipato; Zvavahera Mike Chirenje (BMC Endocrine Disorders)
Abstract Background Proper planning of reproductive health needs for HIV-infected adolescents requires a clear understanding of the effects of HIV infection on adolescents’ pubertal development. Objective To assess the effects of HIV infection on the hypothalamic-pituitary-ovarian (HPO) axis, ovarian reserve and pubertal development in adolescent girls at a tertiary hospital in Zimbabwe. Methods This was a cross-sectional survey of HIV-infected adolescent girls aged 10–19 years, with available CD4 + count results at a tertiary hospital in Zimbabwe. Consecutive sampling was used to select study participants. Pubertal milestones were assessed using the age of menarche and Tanner stage for breast and pubic hair development. Growth was assessed using World Health Organisation growth charts. The HPO axis was evaluated by measuring serum follicular stimulating hormone (FSH), luteinising hormone (LH) and estradiol. The ovarian reserve was assessed in adolescents above 18 years of age by measuring the serum anti-mullein hormone (AMH) levels. Data were analysed in STATA version 13.0, and the results are presented as mean (SD) or median (quartiles) and proportions, as appropriate. Results One hundred and one (101) HIV-infected adolescents were recruited for the study. Menarche, thelarche and pubarche were delayed in 15.9%, 28.6% and 46.8% of the adolescents, respectively. A total of 59.4% had moderate to severe stunting, and 53.5% were either overweight or obese. Most participants had normal serum FSH, LH, and estradiol levels, and there was no association between these hormone levels and growth indicators. The serum AMH levels were reduced in 24.1% of the adolescents. There were no significant differences in the hormonal levels and pubertal development between the WHO CD4 classes. Conclusion HIV infection is associated with stunted growth and delayed sexual maturation with an intact HPO axis in the majority of adolescents. There was no association between growth indicators and FSH and LH levels. The degree of HIV immunosuppression had no significant impact on the HPO axis and pubertal development. A larger study is needed to assess the impact of HIV infection on ovarian reserve. Trial registration : This protocol was approved by the Medical Research Council of Zimbabwe (MRCZ) (reference number MRCZ/A/1730).